Evolving meanings in enterprise education among teachers as learners in a community of practice - Resurreccion, Angelita Bajaro 1955- (University of the Philippines-Diliman, 2019)
This study investigated how teachers enacted enterprise education (EE) in their community of practice foe K-3 learners (aged 5 to 9) in an urban poor community in Quezon City, Philippines. It asks four research questions: (1) What did the teacher learn in EE practice? (2) What meanings of being enterprising did the teachers evolve in their EE practice? (3) How was the evolve framework integrated into the DepEd curriculum? (4) What processes took place that were supportive and and not supportive of EE as it evolved? The inquiry was grounded on Communities of Practice and Social Practice theories. Following a discursive approach from social psychology, the study examined teachers journals, interviews, field notes, and project documents. It augmented the data and analysis from an action research on the ongoing practice, and was informed by social constructivism, where meanings are central and meaning-making is viewed as both constitutive and constructive of knowledge. From the findings, a teaching model was derived from the practice. Teachers built EE on Filipino values around spirituality, social solidarity and enterprise, blending philosophical and practical beliefs about the meaning and purpose of everyday life in school. EE was enacted as a tripartite concept that represents an enterprising disposition consisting of (a) maka-Diyos (godliness), (b) makabayan (good citizenship), and (c) maparaan (being enterprising), with godliness being the core construct. Maparaan was a composite of nine attributes that were constructed as a way to work, as a way to face obstacles, and a way to use resources. Teachers learned how to do EE in three areas: developing a shared repertoire, evolving the EE teaching domain, and manual engagement in a community of practice. The model is a contribution to Educational Psychology, having implications on how teachers connect meanings to curricular content. As a world view, the model contributes to an individual battles against academic challenges in the near term, and poverty in the long term. The report ends with conclusions and recommendations for stakeholders and future researchers.